Hyperon \(Ω\) Production in \(pp\) Collisions at Energy 8 TeV - Dung, Nguyen Thị; Chung, Nguyen Mau; Tam, Tran Minh (Communications in Physics, 2017)
Because strange quark produced copiously in pp collisions, strange hyperon production is one of the ideal tools to investigate the hadronization process and baryon transport theory. We are especially interested in the hyperon Ω production because this baryon contents only strange quark. Our new studies of the pure strange hyperon Ω produced in pp collision at s = 8 TeV are shown in this report. The following strategy is used to reconstruct the strange hyperon Ω. In the LHCb experiment, the hadrons p, π and K are identified by the RICH detector with PT threshold > 100 MeV. Only Lambda (from channel Λ → p + π) with PT > 500 MeV are chosen to combine with kaon daughter particle in order to reconstruct a strange hyperon Ω. The reconstructed particles are accepted as Ω candidates in the case it satisfies several criteria such as its invariance mass must be located within the window mas ± 50 MeV/c2 around the nominal value. More than 63 millions selected events are used for this analysis and about 8100 hyperon Ω candidates are reconstructed.